Skeletal Involvement in Multiple Myeloma: The Radiological Point of View - Cicero, Giuseppe (Journal of Hematology Research, 2019)
Multiple myeloma is one of the most common hematologic malignancies. Bone marrow is typically involved and characterization of osseous lesions, in terms of number, size and localization, is necessary for disease staging and post-treatment assessment. Different imaging modalities can be performed in multiple myeloma evaluation, with a consequential number of information achievable. The aim of this work is to provide a general overview of multiple myeloma radiological findings detectable at X-ray, CT-scan and MRI, with relative advantages and drawbacks for each technique.